2022
DOI: 10.1002/vms3.794
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresistant Newcastle disease vaccine effectively protects SPF, native, and commercial chickens in challenge with virulent virus

Abstract: Background Due to the more stability and a better homogenecity in immune response, the use of thermoresistant vaccines in different chicken types has been increased. Objective This study aimed to evaluate the efficacy of a newly developed Newcastle disease vaccine (ND.TR.IR) originating from I‐2 strain in specific pathogen‐free (SPF) and native and broiler chickens. Methods Following determination of pathogenicity indices on the candidate seed, three efficacy examinations were conducted. In the first experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Some studies, however, have reported the effectiveness of combined inactivated genotype II (La Sota) and genotype VII vaccines in reducing virus shedding ( Mahmoud et al, 2019 ). Previous investigations have shown that inoculation with the ND.TR.IR vaccine, a live genotype I-based strain, conferred satisfactory protection against local genotype VII virulent NDV and the Herts 33 strain ( Abdoshah et al, 2022 ; Hassanzadeh et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, however, have reported the effectiveness of combined inactivated genotype II (La Sota) and genotype VII vaccines in reducing virus shedding ( Mahmoud et al, 2019 ). Previous investigations have shown that inoculation with the ND.TR.IR vaccine, a live genotype I-based strain, conferred satisfactory protection against local genotype VII virulent NDV and the Herts 33 strain ( Abdoshah et al, 2022 ; Hassanzadeh et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antigenic similarity between the circulating velogenic (vNDV) and the vaccine strain could improve the induced vaccinal protection in terms of reduced infectivity and virus shedding [6,[17][18][19]. Vaccination with a live genotype I-based vaccine (ND.TR.IR strain) has protected broiler chickens against the local heterologous genotype VII vNDV and Herts 33 strain in Iran [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The immunity system to disease depends on the existence of a complex of a highly sophisticated and inner immunity system called lymphatic system. Newcastle disease belongs to paramyxoviridae family [1], represented a serious peril on backyard chicken and poultry industry over the world and the spread of this illness may lead to severe trade restrictions on poultry products [2]. Histopathological changes following Newcastle disease virus infection includes infiltration of inflammatory cell, depletion of the lymphoid organs, degeneration and necrosis and the severity of these changes vary according to the strain, health condition of the host, immunity status and dose of the virus.…”
Section: Introductionmentioning
confidence: 99%